OS8.8 Modified chromatin histone marks at noncoding elements are associated with aggressive meningioma subtype. (6th September 2019) - Malta, T; Sabedot, T; Lee, I; Wells, M; Castro, A; Noushmehr, H
Abstract: Background: Although most meningiomas are non-malignant, there is a high recurrence rate among atypical and anaplastic (malignant) meningiomas (grades II/III). In addition, malignant meningioma usually progresses after treatment. Recently, based on DNA methylation, two subgroups of meningioma were described with recurrence-free survival differences (favorable and unfavorable). Epigenetic deregulation at distinct genomic elements such as enhancers can drive changes in gene expression and alter the transcriptional profile of the cancer cells. We seek to understand the mechanisms of meningioma recurrence and progression after initial treatment. Material and Methods: Two favorable and two unfavorable meningioma high grade tumor tissue were selected for this pilot study. Immunoprecipitation (Antibodies) for two different histone modifications (H3K4me3 and H3K27ac) were used to generate genome-wide chromatin-IP sequencing. Genome-wide DNA methylation profile was assessed for 90 meningioma cases including the four samples used in this pilot study. Results: Using a FDR cutoff of 5%, we identified 10, 049 H3K27ac and 5, 752 H3K4me3 chromatin marks that distinguish favorable from unfavorable meningioma. We dichotomized the results into genomic regions overlapping known gene promoters and non-promoters. Promoter associated chromatin changes (H3K27ac and H3K4me3) coincide with DNA methylation changes in aggressive meningioma. The top 1, 000 H3K27ac (sorted by fold difference) without H3K4me3 coincide with highly conserved DNA elements known to be associated with enhancers. These enhancers can drive expression of multiple genes simultaneously. Using DNA methylation differences between favorable and unfavorable meningioma, we will overlap with our unfavorable associated enhancers in order to refine our candidate enhancers for follow up mechanistic studies using aggressive meningioma cell lines. Conclusion: Our preliminary results are the first to unravel the genome-wide chromatin changes associated with unfavorable or clinically aggressive meningioma. Identification of these candidate enhancers will provide knowledge of the role of epigenomics in the development of malignant meningioma and of opportunities for targeted therapy. This project is supported by the Henry Ford Health System, Department of Neurosurgery and the Hermelin Brain Tumor Center Foundation (A30935), United States National Institutes of Health (R01CA222146), and United States Department of Defense (CA170278)